Modernizing Traditional Weaving Tools Through Ergonomic And Environmentally Friendly Design - Rezki Amaliah; Salma Laitupa; Eka Dewi Kartika; Sitti Mutmainnah Syam; Fadli Yasser Arafat Juanda; M Tasbir (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Mandar weaving is a cultural heritage that has important economic and social value for the people of Onang Village, Majene Regency, West Sulawesi Province. However, the yarn winding process that still uses traditional tools causes various problems, such as low work comfort, physical complaints due to non-ergonomic working positions, and low production process efficiency. This community service activity aims to improve the understanding and skills of weavers in applying ergonomic principles and the use of more environmentally friendly yarn winding tools. The method of implementation of the activity is carried out through the stages of preparation, socialization, training, demonstration, mentoring, and evaluation. The activity involved the Mandar Weaving artisan group in Onang Village as the main partner. The results of the activity showed an increase in participants' understanding of the importance of ergonomics in weaving activities, the ability to operate modified yarn winding tools, and increased awareness of the use of environmentally friendly materials. In addition, the application of ergonomic yarn winding tools provides benefits in the form of increased work comfort and efficiency of the yarn winding process. This activity is expected to support increased productivity of artisans while maintaining the sustainability of the Mandar Weaving culture and environmental sustainability in Onang Village.